Intramolecular OH···FC hydrogen bonding in fluorinated carbohydrates: CHF is a better hydrogen bond acceptor than CF2. - Giuffredi, G; Gouverneur, V; Bernet, B (2013)
An intramolecular bifurcated H-bond from the axial HO-2 group to the axial F-4 atom and to the O5 atom of α-D-hexopyranosides in apolar solvents is evidenced in (1)H NMR spectra. The H-accepting properties of the F atom are modulated by the orientation of the O-substituent at the C3 atom and by an additional F atom at the C4 atom.